A model for placing electric vehicle charging stations in megapolis based on the sparrow search algorithm - Sizhuo Du; D. V. Kapski (Системный анализ и прикладная информатика, 2024)
Electric vehicles have such characteristics as low energy consumption and low noise level, and therefore are widely used in modern society, especially for movement in cities and megacities. Active use of electric vehicles (passenger cars and rail and trackless passenger transport) in cities and especially in megalopolises reduces the harmful impact on the ecosystem of the settlement and improves the quality of life in general. Movements become less environmentally hazardous and help to reduce harmful emissions into the atmosphere in places of residence and activities of city residents and tourists. The use of electric vehicles requires their integration with charging stations, and the choice of a reasonable location for the placement of charging stations, which can support the operation of electric vehicles in the largest and large cities, and especially in megalopolises. Based on this, this article examines the problem of placing charging stations for urban electric vehicles. First, the main factors of placing electric vehicle charging stations are analyzed from different points of view, a multi-purpose model for choosing the address of the charging station is built, an algorithmic model is proposed to improve the sparrow search algorithm as the basis for a specific solution method, and finally, the effect of applying the model and solution method is verified by analyzing examples. From the verification results, it can be seen that compared with the traditional genetic algorithm, particle swarm algorithm and other address selection methods, the algorithm proposed in this paper is more optimized, which helps to improve the validity of choosing the address of the electric vehicle charging station and can be widely distributed.